THE LEXICOGRAMMAR OF CUSTOMARY LAW: A TRANSITIVITY ANALYSIS OF SASAK RITUAL DISCOURSE IN WEDDING CEREMONIES - Muliani, Muliani; Ate, Christmas Prasetia (Universitas Negeri Surabaya, 2026)
This research addresses the critical role of ritual discourse in maintaining the socio-cultural fabric of indigenous communities. It examines the intersection of language, ritual, and social structure through a transitivity analysis of Pembayun speech in Sasak wedding ceremonies in Lombok, Indonesia. Applying Systemic Functional Linguistics, the study delves into how specific process types manifest traditional mandates and maintain social equilibrium. By integrating qualitative-descriptive methods with quantitative frequency counts, this study provides a comprehensive analysis of 285 ritual clauses. The analysis reveals a strategic distribution of six process types: Material processes dominate (46.31%), representing social obligations and concrete actions required by customary law, while Relational processes (23.86%) function to validate hierarchical status. To ensure interpersonal harmony, Mental processes (12.28%) express respect and sincerity, and Verbal processes (10.18%) construct ritual dialogue by invoking traditional authority. Furthermore, the spiritual dimension is upheld through Existential processes (4.91%), while Behavioral processes (2.46%) manifest cultural conduct. The study concludes that Pembayun discourse is a sophisticated lexicogrammatical system that actively performs the social and sacred transitions of the Sasak people, illustrating how functional linguistic patterns preserve cultural heritage. It is recommended that future studies incorporate multimodal analysis to capture the non-verbal semiotics of the Sorong Serah ceremony and develop pedagogical frameworks for integrating ritual linguistics into local language preservation curricula.